Research on tourists’ satisfaction with the gastro offer of Novi Sad - Živana Krejić; Snežana Milićević (Anali Ekonomskog fakulteta u Subotici, 2021)
Vojvodina has long been known as an area of high-quality and varied food. In this regard, gastro tourism in its capital is one of the most attractive tourism products. That is the reason why our research was conducted in Novi Sad, aimed to examine the satisfaction of domestic and foreign tourists with the gastro offer of this city. The results of the research show that the gastro offer of Novi Sad is an important motive in attracting both domestic and foreign tourists, but that foreign tourists are still more satisfied with it. Further, there are differences in attitudes between male and female tourists, because male tourists show a higher degree of satisfaction with the gastro offer compared to female tourists, while other socio-demographic characteristics (education and age) are not related to the degree of their satisfaction. The results of the research can be useful in the development of future strategies for the development of tourism in Novi Sad and Vojvodina. They can also serve as a model for analysing tourists’ satisfaction with other forms of tourism offer.